(ε,δ)-approximate counting algorithm for large scale wireless sensor networks - Jing-hua ZHU; Xue-min GUAN (Tongxin xuebao)
The problem of approximate counting for large scale wireless sensor networks was studied.Two approximate counting algorithms,DBT-ACA and DBT-BACA,based on DBT (digital binary tree) protocol were also proposed.The algorithms presented could attain the counting result in O(log logn)time while meeting the(ε,δ)accuracy requirement.DBT-BACA exploits binary search,level-by-level forwarding and delay response technique to effectively reduce the query delay and transmission cost.Theoretical analysis and experimental results show that the proposed algorithms out-perform existing approaches in terms of estimation accuracy,time efficiency and energy cost.